Maternal Atopy Diathesis on The Newborn’s Skin Acidity and Hydration - Osdatilla Esa Putri; Suci Widhiati; Prasetyadi Mawardi; Arie Kusumawardani; Nurrachmat Mulianto; Dwi Hidayah; Pristiawan Endraputra (Jurnal Ners, 2025)
Background: Atopic diathesis, a hereditary predisposition to allergic disorders such as atopic dermatitis, asthma, and allergic rhinitis, is more strongly transmitted maternally. Maternal atopy may influence neonatal skin barrier development, but evidence on its effect on neonatal skin pH and hydration is limited. Methods: This cross-sectional study was conducted at Dr. Moewardi General Hospital, Surakarta, Indonesia, between March–April 2025. Neonates (28–41 weeks gestation), <24 hours old, and delivered by cesarean section were included. Skin pH was measured on the volar forearm and axilla using a calibrated pH meter, and hydration (water and oil content) was assessed with a Skin Tester. Maternal atopy diathesis was classified by the Erlangen Atopy Score (EAS). Results: Twenty-nine neonates were enrolled, comprising 12 with and 17 without maternal atopy. No significant association was found between maternal atopy and neonatal hydration (water: p = 0.460; oil: p = 0.997) or skin pH (p = 0.876). Conclusion: Maternal atopy diathesis was not associated with neonatal skin pH or hydration in the first 24 hours of life. Early neonatal skin physiology appears to be influenced more by intrinsic maturation than maternal atopic status. Longitudinal studies are needed to assess potential delayed effects.